Phospholipase D affects translocation of NPR1 to the nucleus in Arabidopsis thaliana - Janda, Martin; Šašek, Vladimír; Chmelařová, Hana; Andrejch, Jan; Nováková, Miroslava; Hajšlová, Jana; Burketová, Lenka; Valentová, Olga (Frontiers in Plant Science, 2015)
Phytohormone salicylic acid (SA) is a crucial component of plant induced defense against biotrophic pathogens. Although the key players of SA pathway are known, there are still gaps in our understanding of molecular mechanism and regulation of particular steps. In our previous research we showed in Arabidopsis suspension cells that n-butanol, which specifically modulates phospholipase D activity, significantly supresses transcription of pathogenesis related (PR1) gene generally accepted as SA pathway marker. In the presented study, we have investigated the site of n-butanol action in SA pathway. We were able to show in Arabidopsis plants treated with SA that n-butanol inhibits the transcription of defense genes (PR-1, WRKY38). Fluorescence microscopy of Arabidopsis thaliana mutants expressing 35S::NPR1-GFP (nonexpressor pathogenesis related 1) revealed significantly decreased nuclear localization of NPR1 in the presence of n-butanol. On the other hand, n-butanol did not affect nuclear localization of NPR1 in 35S::npr1C82A-GFP and 35S::npr1C216A-GFP mutants constitutively expressing NPR1 monomers. We also observed decreasing effect of n-butanol on ROS production, another important factor in plant response to pathogen attack. Mass spectrometric analysis of plant extracts showed that n-butanol significantly changes metabolic fingerprinting while t-butanol had no effect. We found groups of plant metabolites, influenced differently by SA and n-butanol treatment and we proposed several metabolites as markers for n-butanol action.